2019
DOI: 10.2147/ijn.s184455
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasmall gold nanorods: synthesis and glycocalyx-related permeability in human endothelial cells

Abstract: BackgroundClinical data show shed endothelial glycocalyx (GCX) components in blood samples of atherosclerotic patients, linking atherosclerotic development to endothelial GCX integrity. Healthy GCX has pores no >7 nm, and shed GCX has even larger pores. Therefore, we suggest targeting and treating atherosclerosis-prone blood vessels by using nanoscale vehicles to deliver drugs via the nanoscale GCX as it becomes dysfunctional.Materials and methodsTo test our idea, we investigated permeability of nanoparticles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 61 publications
(124 reference statements)
1
11
1
Order By: Relevance
“…For example, in critical control experiments, we have confirmed that untreated human umbilical vein endothelial cells (HUVEC; Figure a) highly express GCX components such as those targeted by WGA (Figure b) (Mensah et al, manuscript in review), similar to what we observed in healthy RFPEC (Figure e,f). Other GCX components such as HS show low expression (Figure c) in HUVEC, particularly in the absence of physiological flow stimulation, which is usually required for in vitro human EC studies of the GCX . This was contrary to what we observed in RFPEC where HS expression was prominent without flow stimulation (Figure g).…”
Section: Discussioncontrasting
confidence: 78%
“…For example, in critical control experiments, we have confirmed that untreated human umbilical vein endothelial cells (HUVEC; Figure a) highly express GCX components such as those targeted by WGA (Figure b) (Mensah et al, manuscript in review), similar to what we observed in healthy RFPEC (Figure e,f). Other GCX components such as HS show low expression (Figure c) in HUVEC, particularly in the absence of physiological flow stimulation, which is usually required for in vitro human EC studies of the GCX . This was contrary to what we observed in RFPEC where HS expression was prominent without flow stimulation (Figure g).…”
Section: Discussioncontrasting
confidence: 78%
“…However, the low yield and unsatisfied size of GNRs synthesized in this original way make it inappropriate for applications (Scarabelli et al, 2015;Allen et al, 2017), so there appears an endless stream of improvements in accordance with the requirements based on GNRs applications in PTT. GNRs suitable for PTT require good monodispersity, small size (An et al, 2017;Cheng et al, 2019), anisotropy, no toxicity, and the need to be produced in high yields. To obtain ideal GNRs, previous studies have discussed the influence of various factors on the synthesis process (Scarabelli et al, 2015) and adopted different improvement methods, including silver-assisted seeded growth (Nikoobakht and El-Sayed 2003), using CTAB-capped seeds instead of citrate-capped ones, etc., which can help grow GNRs to the desired length (He et al, 2017).…”
Section: Seedless Methodsmentioning
confidence: 99%
“…Larger GNRs represent the higher scattering/absorption ratio, allowing scattering-based applications, such as imaging, whereas smaller GNRs exhibit great potential in PTT toward tumors due to their comparably larger absorption cross-sections. However, traditional synthesis methods of ultrasmall GNRs, by increasing the concentration of seeds added in the growth solution, show a lot of inevitable problems, such as the decreased growth yield and the more by-products, such as nanospheres (Tatini et al, 2014;Chang and Murphy 2018;Cheng et al, 2019;Mbalaha et al, 2019). Therefore, new synthesis strategies of small-sized GNRs should be put forward as soon as possible.…”
Section: Control the Size And Shapementioning
confidence: 99%
“…ECs are covered by endothelial glycocalyx (GCX), which is a complex sugar coat. Due to its unique position, the GCX lines the luminal side of blood vessels and plays an essential role as a vasculoprotective barrier . While there have been numerous studies focusing on DF‐induced endothelial dysfunction, only a few studies have paid attention to DF regulation of the GCX structure and function despite its importance in vascular homeostasis.…”
Section: Introductionmentioning
confidence: 99%